Relationship Between Smoking Cigarettes and Hand Function After Tendon Repair in Men - Mina Nikoufard; Mahrokh Ghahari; AmirHossein Norouzi; Seyed Mehdi Tabatabaee (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims: A proper hand function is essential for performing activities of daily living. Hand injuries can significantly affect participation in these activities. Therefore, any factors that interferes with the treatment of hand injuries and postoperative recovery such as smoking should be controlled. Smoking cigarettes use is a public health problem worldwide. The present study aims to investigate the relationship between smoking cigarettes and hand function after tendon repair in men.Methods: This cross-sectional study was conducted on 40 men (20 smokers and 20 non-smokers) who had undergone at least 10 sessions of physiotherapy and 10 sessions of occupational therapy one and a half months after tendon surgery. In order to collect the information, a demographical form and the shortened disabilities of the arm, shoulder and hand questionnaire (QuickDASH) were used. The collected data were analyzed in SPSS software, version 22.Results: There was a significant difference in hand function after tendon repair between smokers and non-smokers (P=0.006). There was no significant relationship between the number of cigarette consumed per day and hand function (P=0.3)Conclusion: It seems that there is a significant relationship between smoking and hand function after tendon repair, but there is no significant relationship between the number of cigarettes smoked per day and hand function. Individual counseling to smokers with hand injuries and expressing the possible negative effects of smoking on their hand function can increase the effectiveness of rehabilitation in them.